Laboratory investigation of the permeability of gypsum treated Diliman silt - Esguerra, Givette Kristine Y.; Ocampo, April M.
Inadequate soil conditions can be improved through ground improvement methods such as soil treatment through the use of chemical additives. Some studies showed that gypsum, which is cheaper than lime, has a potential to become an alternative to lime in soil stabilization. The main purpose of this study is to investigate the potential of gypsum as a soil stabilizing agent through the determination of the effect of gypsum treatment on the laboratory permeability of Diliman Silt. Diliman Silt was procured and divided into four piles with the following gypsum treatment percentages: 0%, 5%, 10% and 15%. Each treatment was tested for its geotechnical properties through the ASTM tests for sieve analysis, Atterberg limits test, specific gravity test and standard proctor test. Lastly, the permeability was determined through the falling head permeability test, with the use of a makeshift permeameter. The results indicate that as more gypsum is added, there is a decrease in the percentage of very fine particles, a decrease in the specific gravity and a decrease in the optimum moisture content. Also, the addition of gypsum increased the permeability significantly, where the highest factor of permeability increase was seen at the 5% gypsum treatment. The research concluded that the 5% gypsum treatment is the best ground improvement treatment for Diliman Silt due to the highest permeability increase with still a lower unit weight of soil at the least cost.